A Case Study of Social Work Intervention in Behavioural Deviations of Adolescents with Intellectual Disabilities-Based on the Cognitive Behavioural Therapy Model - Cao, Yuxi (Transactions on Social Science, Education and Humanities Research, 2024)
Through reflecting on the case practice of an adolescent with intellectual disability, the article explores how social workers should use their professional skills to intervene in the behavioural deviation of adolescents with intellectual disability under the cognitive-behavioural therapy model. In designing and implementing services, the primary intervention goal of social workers is to help adolescents with intellectual disabilities to correct their misperceptions in personal behaviour, family relationships and social interactions, so as to enable them to have a correct understanding of themselves and to promote the healthy growth of adolescents with intellectual disabilities.